STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM PEMBENTUKAN NILAI-NILAI KARAKTER ISLAMI PESERTA DIDIK DI SMPN 2 NUANGAN - Zakaria Makaminan; Khoirul Anwar; Toha Makhshun (Indonesian Journal of Islamic Studies (IJIS), 2026)
This study aims to describe the strategies of Islamic Religious Education teachers in the formation of Islamic character values ​​in students at SMPN 2 Nuangan, identify supporting and inhibiting factors, and analyze the impact of these strategies on student behavior. The study used a descriptive qualitative approach with a case study design. The research subjects consisted of the principal, three Islamic Religious Education teachers, and Muslim students at SMPN 2 Nuangan. Data collection techniques were carried out through observation, interviews, and documentation. Data were analyzed through the stages of data reduction, data presentation, and conclusion drawing, while data validity was tested through source and technique triangulation, observation persistence, extended participation, and member checks. The results showed that the strategies of Islamic Religious Education teachers in the formation of Islamic character values ​​were carried out through role models, habituation, advice, integration of character values ​​in learning, and supervision of student behavior. Supporting factors included teacher commitment, a conducive school culture, cooperation among school members, and parental support. Inhibiting factors included differences in student backgrounds, lack of family attention, the influence of the social environment, and limited learning time. This strategy has a positive impact on improving students' religious attitudes, discipline, responsibility and good manners.